2007
DOI: 10.1007/s00068-007-7041-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Scapular Fractures Treated Operatively at a Level One Trauma Center

Abstract: Open reduction and internal fixation is associated with anatomic reduction, a low complication rate, and satisfactory functional results at short-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although there are historical reports of operative fixation of the scapula, greater interest has been shown recently in the operative treatment of severely displaced scapula fractures as more positive outcomes emerge out of surgical series. 4,12–38 This literature has indicated that displaced scapular body and neck fractures treated nonoperatively can be associated with complications and poor outcomes such as reduced range of motion, chronic shoulder pain, and concomitant injuries, highlighting the possible benefit that surgical intervention can have for these patients. 16,39–51 Understanding the patterns of fractures in the scapula may lead to improved surgical planning and execution.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are historical reports of operative fixation of the scapula, greater interest has been shown recently in the operative treatment of severely displaced scapula fractures as more positive outcomes emerge out of surgical series. 4,12–38 This literature has indicated that displaced scapular body and neck fractures treated nonoperatively can be associated with complications and poor outcomes such as reduced range of motion, chronic shoulder pain, and concomitant injuries, highlighting the possible benefit that surgical intervention can have for these patients. 16,39–51 Understanding the patterns of fractures in the scapula may lead to improved surgical planning and execution.…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, surgical management, while beneficial, is limited by the concept of conservative treatment. The decision of whether to perform surgical treatment in SBFs (AO/OTA classification: 14-A2.2) remains controversial, 2,6 and there are limited data in the literature for guiding orthopaedic surgeons on deciding on the most appropriate treatment to achieve the best possible clinical outcome for the patient. Current knowledge on the outcomes of surgically treated SBFs has been derived from small and indirect comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Management of scapular body fractures (SBFs; AO/OTA classification: 14-A2.2) has most often been defined as 'benign neglect'. [1][2][3][4] Despite the assessment of the impact of 'benign neglect' by multiple studies, 1,3,[5][6][7] there is a lack of consistency regarding its effectiveness in preventing or avoiding complications, or its impact on longer-term outcomes. This controversy remains due to small sample sizes and low rates of complications induced by SBFs, which limits the power of these studies.…”
Section: Introductionmentioning
confidence: 99%